An introductory guide to artificial intelligence for legal professionals - González-Espejo, María Jesús; Pavón, Juan (Kluwer Law International B.V., 2020)
This introduction to AI will help practitioners in tax law, labour law, competition law and intellectual property law to understand what AI is, what it serves, what is the state-of-the-art and the potential of this technology, how they can benefit from its advantages and what are the risks it poses. It will be beneficial for people in the labour market, and the economic and business sector seeking legal advice. Also, policymakers will recognize the urgent need to formulate rules to properly manage the future of AI.